Usefulness of Endoscopic Transpapillary Tissue Sampling for Malignant Biliary Strictures and Predictive Factors of Diagnostic Accuracy - Hiroki Tanaka; Shimpei Matsusaki; Youichirou Baba; Yoshiaki Isono; Tomohiro Sase; Hiroshi Okano; Tomonori Saito; Katsumi Mukai; Tetsuya Murata; Hiroki Taoka (Korean Society of Gastrointestinal Endoscopy, 2018)
Background/Aims It is sometimes difficult to distinguish between malignant and benign biliary strictures using imaging studies alone, and pathological diagnosis is necessary. The aim of this study was to determine the usefulness of endoscopic transpapillary tissue sampling and factors predictive of diagnostic accuracy. Methods From April 2008 to December 2014, 136 patients underwent endoscopic transpapillary tissue sampling for malignant biliary strictures. The cytological and histological findings were reported as negative, suspicious, or positive. Suspicious and positive findings were defined as pathologically positive. Results The sensitivity was 65.0% for forceps biopsy, 49.5% for brush cytology, 46.2% for bile aspiration cytology, and 21.9% for endoscopic nasobiliary drainage cytology. The combination of these procedures improved the sensitivity (72.8%). Endoscopic transpapillary tissue sampling was more sensitive for lesions of biliary origin (91.4%) than for extrabiliary lesions (66.3%). In surgical cases, the sensitivity for tumors with an infiltrative growth pattern (53.3%) was significantly lower than for a tumor with an expanding or intermediate growth pattern (87.5%). Conclusions Combining procedures can improve diagnostic accuracy. It may be possible to predict the sensitivity of endoscopic transpapillary tissue sampling by evaluating the etiology and tumor growth pattern using preoperative imaging studies.